A survey on resolving security issues in SaaS through software defined networks. (1st January 2021) - Shyam, Gopal K.; Theja, Reddy Sai Sindhu
The key ingredient in the success of Software-as-a-Service (SaaS) is based upon the client's satisfaction. Sensitive data acquired from the organisations are processed by the SaaS applications and stored at the SaaS provider end. All data flow over the network needs to be secured to avoid leakage of sensitive data. However, upon preliminary investigation, security is found to be the foremost issue that hampers the growth of confidence in the entrepreneurs for data deployment. This paper mainly focuses on different security issues in SaaS. Further, we analyse the security issues derived from the use of Software Defined Networking (SDN) and elaborate on how it helps to improve security in SaaS. Additionally, comparisons between current solutions and SDN solutions are made. Hence, this work aims at giving new directions to the researchers, specifically in the domain of SaaS, in understanding security issues and planning possible countermeasures.